Antimycobacterial Activity of Some Synthesized Fluorinated Benzothiazolo Imidazole Compounds - B. S. Sathe; E. Jaychandran; G. M. Sreenivasa; V. A. Jagtap (E-Journal of Chemistry)
4-Fluoro-3-chloroanilline treated with potassium thiocyanate in presence of glacial acetic acid and bromine was converted into 2-amino-6-fluoro-7-chlorobenzothiazole, resulting into 2-amino benzothiazole. The synthesized compound in presence of 2-phenyl-4-benzylidine-5-oxazolinone refluxed in pyridine to obtain 2-(2-phenyl-4-benzylidenyl-5-oxo-imidazolin-1-yl amino)-6-fluoro-7-substituted(1,3)benzothiazoles. The above said compound was treated with ortho, meta and para nitroanillines, ortho, meta, para chloroanillines, morpholino, piperazine, diphenylamine in the presence of DMF to obtain different derivatives. Some compounds showed promising anti-microbial activity.